2022
DOI: 10.24093/awej/covid2.5
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Teachers and Students’ Perceptions towards Emergency Online Learning Intensive English Writing Course during COVID-19 Pandemic

Abstract: For ages, teaching and learning face-to-face has been very popular and considered the best way to achieve knowledge and accomplish academic activities. However, during the Covid-19 Pandemic, where on the one side, the whole world was searching for a solution to cope with the situation on the other side online learning demonstrated a substantial alternative. The present paper aimed to investigate the teachers and students’ perceptions of the emergency online learning process, especially for intensive English wr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…In addition, in line with Bui's study (2022), students' motivation needs to be increased, especially those with low ability in digital literacy (Tarihoran et al, 2022). Another similar challenge is about plagiarism (Kurtianti et al, 2021;Setyowati et al, 2021;Sheerah et al, 2022) which encourages the participants of this study to introduce thesaurus and various paraphrasing tools to minimize this issue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in line with Bui's study (2022), students' motivation needs to be increased, especially those with low ability in digital literacy (Tarihoran et al, 2022). Another similar challenge is about plagiarism (Kurtianti et al, 2021;Setyowati et al, 2021;Sheerah et al, 2022) which encourages the participants of this study to introduce thesaurus and various paraphrasing tools to minimize this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Other challenges, more than technical problems and an internet connection, for online writing classes during the pandemic, include students' low motivation (Bui, 2022), plagiarism (Kurtianti et al, 2021;Setyowati et al, 2021;Sheerah et al, 2022), and interaction (Tusino et al, 2021). Nevertheless, Stewart's (2021) investigation on one part of the community of inquiry framework related to interaction called social presence concluded that even though the interaction in the writing class was virtual and not physical, the students considered their teacher and classmates as real persons having real interactions by expressing their sense of humor and sharing emojis.…”
Section: Efl Online Writing Classes During the Pandemicmentioning
confidence: 99%
“…During the pandemic, students were forced to transition from a physical to a virtual learning environment. Consequently, some universities provided students with high flexibility concerning material resources by allowing them to access video recordings at any time (Sheerah et al, 2022;Guskaroska et al, 2022). Additionally, students can learn ideas and solve problems at their own pace and under their own time constraints through pre-recorded lectures.…”
Section: Students' Perceptions Of Emergency Remote Teaching and Learningmentioning
confidence: 99%
“…The negative perceptions were its inappropriateness for productive skills and over complexity when handing collaborative tasks through the use of 'Discussions' or 'Open Board.' More specific to teaching EFL writing, one study (Sheerah, Yadav, Allah, & Abdin, 2022) investigated Saudi Arabian teachers' perceptions of online writing courses during the pandemic, revealing that while overall teacher satisfaction levels were high, there were a number of concerns. The first of which is related to plagiarism.…”
Section: Perceptions Of Canvasmentioning
confidence: 99%